The Effect of Physical Activity on Respiratory Rate in Humans - Artanti, Nabilah; Fauziah, Fadilatul; Zahra, Mutia; Fitri, Auliani; Maulina, Cindy; Elin, Elin; Hendriyani, Mila Ermila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The human respiratory system plays a vital role in gas exchange, particularly the intake of oxygen (O₂) and the removal of carbon dioxide (CO₂), which are essential for cellular metabolism. Respiratory rate is a physiological parameter that reflects pulmonary ventilation activity and varies according to the intensity of physical activity. This study aimed to analyze the effect of physical activity on respiratory rate in five participants. A simple experimental method was used, involving three activity conditions: resting (sitting), walking, and running. Respiratory rate was measured for one minute under each condition with three repetitions, and the data were analyzed descriptively. The results showed that respiratory rate increased with higher levels of physical activity: 21–28 breaths per minute at rest, 24–48 during walking, and 30–86 during running. This increase indicates a physiological response to meet the body’s elevated oxygen demand and CO₂ elimination during exertion. Therefore, respiratory rate can serve as an important indicator of physical adaptation, fitness level, and respiratory system efficiency. These findings have practical implications for health monitoring, physical education, and early detection of respiratory stress during exercise or clinical assessment.